Random attractors for ambiguously solvable systems dissipative with respect to probability - Kapustyan, O. V. (Ukrains’kyi Matematychnyi Zhurnal, 2004)
We prove a theorem on the existence of a random attractor for a multivalued random dynamical system dissipative with respect to probability. Abstract results are used for the analysis of the qualitative behavior of solutions of a system of ordinary differential equations with continuous right-hand side perturbed by a stationary random process. In terms of the Lyapunov function, for an unperturbed system, we give sufficient conditions for the existence of a random attractor.